EVALUATION OF THE EFFECTIVENESS OF EXTRAOCULAR MUSCLE FENESTRATION SURGERY IN THE TREATMENT OF HORIZONTAL SENSORY STRABISMUS (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the effectiveness of extraocular muscle fenestration surgery in the treatment of horizontal sensory strabismus.Subjects and Methods: A prospective descriptive study was conducted on 37 patients diagnosed with horizontal sensory strabismus who underwent extraocular muscle fenestration in the Pediatric Ophthalmology Department at Vietnam National Eye Hospital from December 2024 to July 2025. Both male and female patients aged ≥16 years were included.Results: The study included 37 patients (mean age 27.2 ± 10.8 years), with the majority aged 16–40 years. The mean preoperative deviation angle was 33.5 ± 12.9 PD in sensory exotropia and 37.7 ± 11.8 PD in sensory esotropia. The surgical success rate (
Keywords: sensory strabismus, extraocular muscle fenestration, amblyopia.